Current Treatment Update for Anterior Cruciate Ligament Tears in Adolescence: A Narrative Review - Yushan, Rafael Marvin; Winaga, Handriadi; Singjie, Leonard Christianto (Indonesian Hip and Knee Society (IHKS), 2024)
To follow up regarding orthopedic updates in respect of the treatment of ACL tears in adolescence. The methods we performed a comprehensive literature search from four databases to synthesize a narrative review of available evidence on the recent update of ACL treatment in adolescence. The results is conservative treatment remains preferred for partial ACL tears in adolescence. Some surgeons have favored non-operative or delayed surgical treatment until skeletal maturity has reached or after a failed trial of non-operative management. However, adolescent patients who delayed ACLR for more than 12 weeks had increased risk of meniscal pathology and irreparable meniscal tears by a 4.3 and 3.2 times, respectively. Various ACL reconstruction techniques for adolescents have developed to respect growing physes, these are physeal sparing (extraphyseal and all-epiphyseal), partial transphyseal, and transphyseal. The conclusions is early operative treatment of ACL injury is preferred compared to non-operative or delayed treatment. The reconstruction techniques were adjusted to each patient's potential for growth, the facilities' capabilities, and the surgeons' skills. High-growth potential patients should still undergo surgery using a technique with the slightest manipulation of growth cartilage.